A Case of Multiple Sclerosis—Like Relapsing Remitting Encephalomyelitis Following Allogeneic Hematopoietic Stem Cell Transplantation and a Review of the Published Literature - Das, Joyutpal; Gill, Atta; Lo, Christine; Chan-Lam, Natalie; Price, Siân; Wharton, Stephen B.; Jessop, Helen; Sharrack, Basil; Snowden, John A. (Frontiers in Immunology, 2020)
Complications involving the central nervous system (CNS) occur in 9-14% of patients following allogeneic haematopoietic stem cell transplantation (HSCT), including stroke-like episodes, demyelination, encephalitis and nonspecific neurological symptoms. Here we report the first case of a multiple sclerosis (MS) like presentation following allogeneic HSCT that was treated with ‘domino’ autologous HSCT. A 53-year-old male was treated with allogeneic HSCT for lymphoid blast transformation of chronic myeloid leukaemia. Ten months later he presented with confusion, slurred speech, left sided facial weakness and ataxia. A magnetic resonance imaging brain scan showed multiple enhancing tumefactive lesions. The neuromyelitis optica (NMO) and myelin oligodendrocyte glycoprotein (MOG) antibodies were negative. After extensive investigations for infections, autoimmune disorders and recurrence of malignancy, he underwent brain biopsy, which showed demyelination. Although symptoms improved with corticosteroids, relapse occurred after five months. In the absence of any systemic features suggesting graft versus host disease (GvHD), his presentation was thought to be more compatible with MS than other CNS demyelinating disorders. The disease followed an aggressive course and did not respond to two disease modifying therapies (DMTs) for MS (glatiramer acetate and natalizumab). He became wheelchair bound within 2 years. The patient was treated with ‘domino’ autologous HSCT, which produced a transient response, but failed to induce long-term remission. Despite further treatment with ocrelizumab, a third DMT, he died of progressive disease. This unique case highlights the rare complication of a severe demyelinating neuroinflammation following allogeneic HSCT which represents either ‘pure’ CNS GvHD or post-transplant immune dysregulation. In the literature, there is only a handful of cases reporting CNS demyelination following allogeneic HSCT. There is a lack of understanding and consensus regarding the existence of ‘pure’ CNS GvHD. Reporting of such cases will increase our awareness. In this case, the neuroinflammation was steroid responsive initially, but resistant to three DMTs. We highlight the feasibility of a ‘domino’ autologous HSCT procedure in this context, albeit with limited response at the late stage of disease progression and discuss whether standard GvHD treatment would be more effective than MS-directed treatment, even when systemic GvHD is not present.